mlo5, a resistance gene effective against a biotrophic pathogen (Blumeria graminis fsp. hordei) confers enhanced susceptibility of barley to the necrotrophic fungus Bipoláris sorokiniana (teleomorph: Cochliobolus sativus)
The barley resistance gene m/o5 determines race non-specific resistance to the biotrophic powdery mildew pathogen Blumeria graminis f.sp. hordei. On the other hand, we have shown that barley lines that contain the mlo5 gene display enhanced susceptibility to the necrotrophic fungus Bipoláris sorokiniana (teleomorph: Cochliobolus sativus) and its toxic culture filtrate (Kumar et al. 2001). Enhanced susceptibility to necrotic disease symptoms was linked to increased accumulation of hydrogen peroxide (H